Localization of eosinophil granule major basic protein in human basophils (The Rockefeller University Press, 1983)
In experiments using an immunofluorescent method to localize human eosinophil granule major basic protein (MBP) in cells and tissues, a small number of cells stained for MBP that subsequently could not be identified as eosinophils. Because the Charcot-Leyden crystal protein, another eosinophil protein, was recently identified in basophils, we tested whether MBP might also be a constituent of blood basophils. Highly purified, eosinophil-free basophil suspensions were prepared using the fluorescence-activated cell sorter (FACS) to sort basophil- containing mononuclear cell preparations stained with fluorescein- conjugated sheep IgG anti-human IgE antibody. Using these FACS-purified basophils, we found that: (a) enrichment for surface IgE-positive cells (greater than 95% basophils) by FACS also enriched for cells staining for MBP by immunofluorescence; (b) MBP appeared to be localized in the histamine-, heparin-containing granules; (c) significant quantities of MBP were measurable by radioimmunoassay (RIA) in freeze-thaw detergent extracts of purified basophils; and (d) RIA dose-response curves for extracts of purified eosinophils and basophils had identical slopes. The MBP content of basophils from normal individuals averaged 140 ng/10(6) cells, whereas purified eosinophils from normal donors and patients with the hyper-eosinophilic syndrome averaged 4,979 and 824 ng/10(6) cells, respectively. MBP was also detected by immunofluorescence and RIA in cells obtained from a patient with basophil leukemia, although the MBP content for basophil leukemia cells was lower than that for normal basophils. We conclude that basophils contain a protein that is immunochemically indistinguishable from eosinophil granule MBP.